PENERAPAN ACCURATE ACCOUNTING DALAM MENYUSUN LAPORAN KEUANGAN PADA CV ANEKA GRAFIKA SEBAGAI DASAR PENGUKURAN KINERJA KEUANGAN - Irfansyah, Muhammad; Kamayanti, Ari; Widiastuti, Retno (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The purpose of this research is to describe the implementation of accurate accounting in preparing financial statements on CV Aneka Graphics as a basis for measuring financial performance. This type of research uses applied research. Data collection techniques use interviews and documentation. The conclusion of this research was that the entity recorded using the manual Excel application. The results of implementing Accurate Accounting can help entities record effectively and efficiently, can help create financial reports automatically, and can help measure and broadcast financial performance easily.